(3eNJGQGJ TYQjIs - (3eLghds ((3YHOGdeMSf Hf eMeO Hf Ydj s)
(3ChdgG (B:s
(3hbGd jUa GdTGe aj bUjOI(B: (3oYfjJ HTQb GdCQV WhQkG hZQHgG oCWha aj CaGbgG hCSjQgG ade CQ eKd GdTGe OGQ EbGeI dQGM jZGOjgG hcGS ojOjQgG s
(3BNQgG (B:s
(3ef GdeNJGQ hEfc CMdi aj Lahfj ef GdcQi hCYPH WYekG aj aDGOj ef GdCef Je GdcJGH hGdMeO ddg s
(3dCHj fhGS, hGHf GdQhej, hGHf GdeYJR, hcTGLe, hGdeJfHj, hGdbGVj GdJfhNj, hGdhRjQ GdegdHj, hGdQVis
(3eged GdfbW CMjGfkGs
(3ajg HYV GdVHWs
(3JdGgG fbhd CNQi cKjQI aj fMh (B174 (3hQbI HNW eNJda haj ehVhYGJ TJi s
(3eged GdfbW CMjGfkGs
(3ajg HYV GdVHWs
Keywords: (3GdCOHs